„Gazeta Łódzka” i jej miejsce w społeczno-kulturalnym życiu Łodzi. Początki i współczesność - Robak, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Article covers the topic of “Gazeta Łódzka” (“Gazeta Wyborcza Łódź”), local supplement added to national newspaper “Gazeta Wyborcza”. In the article criteria of local media and their functions were analysed. Their influence on local societies is also considered. Two periods of newspaper’s activity are concerned – beginning of the nineties of twentieth century and the beginning of the twentieth-first century. Information were gathered by author from analysis of the newspaper and interviews with Piotr Wesołowski the deputy of chief redactor and workers of Advertising Department. History and activity of “Gazeta Łódzka” is presented from perspective of fulfilling the determinants of local press and methods of readers elicitation. Examples of involvement in problems of Łódź inhabitants and achievements of newspaper’s journalists are shown. There were taken into consideration non-standard activities such as charitable actions and ones that promote culture also, not only materials published in the newspaper. Results of deliberations allow to think that “Gazeta Łódzka” is one of the factors that influences identity of the city and is helping to develop positive image of Łódź in the united Europe.